1970
DOI: 10.1177/002199837000400405
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Graphite Fiber Surfaces with Raman Spectroscopy

Abstract: Raman spectroscopy is used to characterize the fiber surface of graphite and carbon fibers. A correlation exists between the Raman spectrum of the fiber surface and the shear strength of the com posite. Effects of surface treatments are reflected in the Raman spec trum as well as the shear strength of the composite. Many graphite fibers have a weak surface layer where the graphite planes are oriented parallel to the surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
199
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 455 publications
(209 citation statements)
references
References 3 publications
9
199
0
1
Order By: Relevance
“…The R ratio decreased with the increase of La. 5) Thus, the R ratio can be used to evaluate perfection degree of graphite structure. Katagiri et al 8) made the map using R ratio and half width of peak for the more precise characterization of materials.…”
Section: Evaluation Methods Of Carbonaceous Materialsmentioning
confidence: 93%
See 2 more Smart Citations
“…The R ratio decreased with the increase of La. 5) Thus, the R ratio can be used to evaluate perfection degree of graphite structure. Katagiri et al 8) made the map using R ratio and half width of peak for the more precise characterization of materials.…”
Section: Evaluation Methods Of Carbonaceous Materialsmentioning
confidence: 93%
“…with Raman Spectrum Analysis There have been many reports on the evaluation method of ordered materials with Raman spectrum analysis, namely, 1) peak intensity ratio, 5) 2) peak area ratio, 6) 3) half width of peak. 7) The peak ratio of D band peak to G band peak is called R ratio, RϭI D /I G .…”
Section: Evaluation Methods Of Carbonaceous Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Raman results can be used to get some insight in this problem. In fact Tuinstra and Koenig demonstrated that the intensity ratio I D /I G is inversely proportional to the in plane crystallites size and proposed a formula which is valid for the 514.5 nm excitation wavelength only [22,23]. A general equation, that can be used for every wavelength, is given in [17]:…”
Section: Resultsmentioning
confidence: 99%
“…These parameters are L a and L c . 19,20 L a is the average diameter of the graphite layer, whereas L c divided by the interlayer spacing (approximately 3.35Å) gives the number of layers. Well-crystallized graphite can have L a values up to several thousand angstrom, whereas microcrystalline graphite, also referred to as amorphous graphite, can have L a values as low as 20-30Å.…”
Section: Graphitementioning
confidence: 99%